Assessing interdependent operational, tactical and strategic risks for improved utility master plans. (1st May 2015) - Luís, Ana; Lickorish, Fiona; Pollard, Simon
Abstract: Risk management plays a key role in water utilities. Although risk tools are well-established at operational levels, approaches at the strategic level are rarely informed by systemic assessments of the water supply and lack a long-term perspective. Here, we report a baseline strategic risk analysis, founded on a systemic analysis of operational risks developed 'bottom-up' and validated in a large water utility. Deploying an action-oriented research method, supported by semi- structured interviews with in-house water utility risk experts, deep connections are established between operational risk and strategic risk that surpass those existing elsewhere in the sector. Accessible presentational formats – influence diagrams, risk "heat-maps" and supporting narratives are used to promote Board-level risk discussions, and characterise a baseline set of strategic risks core to forward utility master planning. Uniquely, the influence of operational events, exposures and potential harms, together with the mitigating measures in place to mediate these risks are linked to corporate objectives on business sustainability, profitability, water quality, water quantity, supply disruption and reputation. Graphical abstract: Highlights: A novel approach for strategic risk management in water utilities is presented. Connections between risks at operational and strategic levels are made evident. We demonstrate how physical, financial and reputational risks are interrelated. Cognitive mapping of pathways from events, exposures to harms to corporate risks. The approach developed was tested at full-scale in a large water utility.